First principles predictions of thermophysical properties of refrigerant mixtures - Oakley, Mark T.; Hainam, Do; Hirst, J.D.; Wheatley, Richard J. (American Institute of Physics, 2011)
We present pair potentials for fluorinated methanes and their dimers with CO2 based on ab initio potential energy surfaces. These potentials reproduce the experimental second virial coefficients of the pure fluorinated methanes and their mixtures with CO2 without adjustment. Ab initio calculations on trimers are used to model the effects of nonadditive dispersion and induction. Simulations using these potentials reproduce the experimental phase-coexistence properties of CH3F within 10% over a wide range of temperatures. The phase coexistence curve of the mixture of CH2F2 and CO2 is reproduced with an error in the mole fractions of both phases of less than 0.1. The potentials described here are based entirely on ab initio calculations, with no empirical fits to improve the agreement with experiment.